Pneumococcal carriage in children in Ulaanbaatar, Mongolia before and one year after the introduction of the 13-valent pneumococcal conjugate vaccine - von Mollendorf, Claire; Dunne, Eileen M.; La Vincente, Sophie; Ulziibayar, Mukhchuluun; Suuri, Bujinlkham; Luvsantseren, Dashtseren; Narangerel, Dorj; Ortika, Belinda D.; Pell, Casey L.; Nation, Monica L.; Alamrousi, Ahmed; Hinds, Jason; et al. (Vaccine, 2019)
Nasopharyngeal carriage of Streptococcus pneumoniae precedes disease, is the source of pneumococcal community spread, and the mechanism for herd protection provided by pneumococcal conjugate vaccines (PCVs). There are few PCV impact studies in low- and middle-income countries, particularly in Asia. In 2016, Mongolia introduced the 13-valent PCV (PCV13) in a phased manner using a 2 + 1 schedule, with catch-up. We aimed to assess the impact of PCV13 introduction on nasopharyngeal pneumococcal carriage and density in children in Mongolia. We conducted two cross-sectional carriage surveys (pre- and one year post-PCV) at community health clinics in two districts of the capital city, Ulaanbaatar in both May-July 2015 and 2017. The study analysis included 961 children too young to be vaccinated (5–8 weeks old) and 989 children eligible for vaccination (12–23 months old). Pneumococci were detected by quantitative real-time PCR and molecular serotyping performed using DNA microarray. One year post-PCV introduction, PCV13 serotype carriage reduced by 52% in 12–23 month olds (adjusted prevalence ratio [aPR] 0.48 [95% confidence interval [CI] 0.39–0.59]), with evidence of non-PCV13 serotype replacement (aPR 1.55 [95% CI 1.30–1.85]), compared with the pre-PCV period. In 5–8 week olds, PCV13 serotype carriage reduced by 51% (aPR 0.49 [95% CI 0.33–0.73]) with no significant change in non-PCV13 serotype carriage (aPR 1.10 [95% CI 0.83–1.46]). An increase was observed in both PCV13 and non-PCV13 pneumococcal density post-PCV introduction. Antimicrobial resistance (AMR) genes were common, with 82.3% of samples containing at least one of the 10 AMR genes assessed. This study demonstrates substantive PCV13 impact on pneumococcal carriage one year post-vaccine introduction in Mongolia. The reductions in PCV13 serotype carriage are likely to result in reductions in pneumococcal disease including indirect effects. Increases in non-PCV13 serotypes require further monitoring.